Natural reproduction in tropical buffalo herds - Laura Gómez Estrada (Revista Científica)
Reproduction is one of the most important aspects of farm management that, combined with genetics, allows the productive system to develop and meet minimum productivity standards for sustainability and market demands. Despite the close phylogenetic relationship to cows, the buffalo has many differences in estrus expression, follicle diameter size at ovulation, and progesterone profiles (Bertoni et al., 2020). Seasonality is very marked in buffaloes. Knowledge of natural reproduction is the first step for the successful application of reproductive biotechnologies. This study analyzes the reproductive parameters during 2023 of two Colombian buffalo herds located in different regions: Uraba (7.7580555,-76.6552777) and Puerto Boyaca (5.9387942,-74.577977,1). Animals were maintained in low tropical rainforest with a temperature of 23–32°C, annual rainfall (2300 mm3 and 570 mm3), altitude (2 – 190 masl) for Uraba and Puerto Boyaca, kept in natural and improved pastures (Brachiaria humidicola or B. decumbens), with water and minerals ad libitum. Pregnancies were obtained by natural mating (1/55 male-female). A reproductive check-up was done by rectal palpation every three months. Data were managed using specialized software for herd management.  Descriptive statistics of parameters are presented, and comparisons were performed using the Mann-Whitney test. Data from 624 and 254 were analyzed, average age 4.80 (2.8-14.0) and 8,98 years (3,5-19), birth rate 79.38% and 82.01%, inter calving period 435 and 452 days, calving-conception 133 and 126, age to first calving 40.1 and 37.0 for the herds located in Uraba and Puerto Boyaca, respectively; 91.1% and 87.6% of the dry buffaloes are pregnant. There are no statistical differences in the parameters within the herds. As expected, the reproductive parameters of the two buffalo herds are better than the average for cows of the same region. The large number of dry-pregnant females is evidence of the effect of seasonality since, at the time of writing this summary (June 2023), we are in an unfavorable reproductive season in Colombia. The two farms in the tropical region, 504 km away, showed comparable reproductive parameters. First calving is low compared to cows. Rapid onset of ovarian activity allows breeders to apply reproductive biotechnologies in early postpartum to improve reproductive outcomes.